2020
DOI: 10.1007/s13355-020-00686-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic prediction of acaricide resistance gene frequency using quantitative real-time PCR with resistance allele-specific primers in the two-spotted spider mite Tetranychusurticae population (Acari: Tetranychidae)

Abstract: Due to the development of acaricide resistance in Tetranychus urticae, a rapid and accurate monitoring method for acaricide resistance gene frequency is required for resistance management.In this study, we developed a new diagnostic gene frequency prediction method, using quantitative real-time PCR with allele-specific primer sets, for mutation of I1017F in chitin synthase I, G126S in mitochondrial cytochrome b, and H110R in the PSST subunit of mitochondrial electron transport complex I, which are involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Moderate to high RRs to METI‐I acaricides have been reported previously 13,28,68 . A point mutation in psst/NDUFS7 of complex I has previously been associated with resistance to METI‐Is in both Tetranychus and Panonychus species, 9,69,70 and this mutation was also identified in the Trz population, although not fixed. In addition, an A55T substitution was also uncovered, but this mutation was not in a conserved region or near the binding site of METI‐Is.…”
Section: Discussionmentioning
confidence: 85%
“…Moderate to high RRs to METI‐I acaricides have been reported previously 13,28,68 . A point mutation in psst/NDUFS7 of complex I has previously been associated with resistance to METI‐Is in both Tetranychus and Panonychus species, 9,69,70 and this mutation was also identified in the Trz population, although not fixed. In addition, an A55T substitution was also uncovered, but this mutation was not in a conserved region or near the binding site of METI‐Is.…”
Section: Discussionmentioning
confidence: 85%
“…Maeoka et al . (2020) demonstrated that a general ΔΔCq method without restriction enzyme treatment could be used for allele-frequency measurement if a specific primer set were to be designed to amplify only the R allele at the target locus.…”
Section: Modelmentioning
confidence: 99%
“…Although Eq. 11 is defined for the RED-ΔΔCq method, it is also applicable to the ΔΔCq method by Maeoka et al . (2020) by substituting and to and , respectively.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations